Creative Economy as a Career Path for Gen Z: Learning from the MBKM Internship Program for UNPAB Students with PT. Konsultan Media Digital - Supiyandi, Supiyandi; Amelia, Nanda; Putri, Dinda Wijaya (LKP KARYA PRIMA KURSUS, 2025)
Internship Program MBKM (Merdeka Belajar Kampus Merdeka) has become one of the important initiatives in bridging the world of education with the world of industry, especially for students who want to deepen practical skills in certain fields. This article discusses the empowerment of Gen Z's potential in the creative economy through the MBKM internship program involving students of Panca Budi Development University (UNPAB) and PT. Konsultan Media Digital. The creative economy, as a rapidly growing sector, provides many opportunities for the younger generation, especially Gen Z, to develop innovative skills, entrepreneurship, and digital skills that are urgently needed in this digital era. Through a collaboration between UNPAB and PT. Konsultan Media Digital, students have the opportunity to be directly involved in creative projects, such as social media management, graphic design, digital content creation, and digital marketing. The learnings gained during this internship include not only technical knowledge, but also an understanding of the industry dynamics and the challenges of running a digital-based business. Empowering Gen Z in the creative economy through MBKM internships is expected to open up wider career opportunities, both in the creative industry and in creating independent businesses. The results of this program show that students not only gain relevant work experience, but also improve their skills in creative thinking, innovation, and teamwork. This program has a positive impact in shaping the profile of graduates who are ready to compete in the growing creative industry. Therefore, the MBKM internship with PT. Konsultan Media Digital is a strategic step in preparing Gen Z to play an active role in the creative economy.